The Effect of Company Size and Leverage on Tax Avoidance (Empirical Study on Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2017-2019 Period) - Ago Sahputra; Hernadianto Hernadianto; Ahmad Sumarlan; Diah Khairiyah (Journal of Management, Economic, and Accounting, 2026)
Tax avoidance or commonly called tax avoidance is an effort to avoid tax legally that does not violate tax regulations by taxpayers by trying to reduce the amount of tax by looking for regulatory weaknesses (loopholes). The formulation of the problem in this study is whether company size and leverage affect tax avoidance. This study aims to see the effect of firm size and leverage on tax avoidance.Quantitative research method, The object of this research is a manufacturing company listed on the Indonesian stock exchange during the 2017-2019 period, with a purposive sampling method. The number of observations in this study amounted to 144 observations. By using multiple regression analysis technique, it can be concluded that firm size has a positive effect on tax avoidance with a sig value of 0.000 <0.05 and a t-count value of 3.941. Leverage has a positive effect on Tax Avoidance with a sig value of 0.012 <0.05 and a t-count value of 2.577. Company Size and Leverage have an effect on Tax Avoidance with a sig value of 0.000 <0.05 and an F value of 11,377.